2021
DOI: 10.35833/mpce.2020.000908
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Inertia Estimation Method of DFIG-based Wind Farm with Additional Frequency Control

Abstract: With the increasing penetration of wind power, using wind turbines to participate in the frequency regulation to support power system has become a clear consensus. To accurately quantify the inertia provided by the doubly-fed induction generator (DFIG) based wind farm, the frequency response model of DFIG with additional frequency control is established, and then by using Routh approximation, the explicit expression of the virtual moment of inertia is derived for the DFIG gridconnected system. To further enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The results of simulation were indicated that the proposed frequency control method is useful to enhance the capability of frequency regulation under several patterns of wind speed and the penetration levels especially for power systems with highly wind generation. In [138], Chen et al introduced a technique for the estimation of the virtual moment of inertia given by a DFIG-based wind farm with additional frequency control. Routh approximation was used to derive the explicit formulation of the virtual moment of inertia for grid connected DFIG-based WECS.…”
Section: Recent Frequency Control Methodsmentioning
confidence: 99%
“…The results of simulation were indicated that the proposed frequency control method is useful to enhance the capability of frequency regulation under several patterns of wind speed and the penetration levels especially for power systems with highly wind generation. In [138], Chen et al introduced a technique for the estimation of the virtual moment of inertia given by a DFIG-based wind farm with additional frequency control. Routh approximation was used to derive the explicit formulation of the virtual moment of inertia for grid connected DFIG-based WECS.…”
Section: Recent Frequency Control Methodsmentioning
confidence: 99%
“…Considering the orderly synchronization of frequency-regulated power between the DFIG units and the SG units in the grid, the quantification method needs to be determined according to the inertial response characteristics of the SG units. Equation ( 6) expresses the inertial response principle of an SG unit [30,31], where ∆T e , T m , and T e are the electromagnetic torque increment, mechanical torque, and electromagnetic torque of the SG, respectively, and H g represents the inertial time constant, f is the system frequency, ∆P e is the electromagnetic power increment, and superscript * indicates the per-unit value. Methods for controlling the virtual inertia of DFIG units include the P-D algorithm, curveshifting method, and FFR; among these, the frequency regulation characteristics of the P-D algorithm are most similar to those of SG units, as shown by Equation (7) [32].…”
Section: Quantization Of Virtual Inertia At the Dfig Levelmentioning
confidence: 99%
“…However, the mismatch between the fast dynamics of DFIGs and the existing phasor measurement reporting rate is ignored in these studies. Note that DFIGs generally have a small capacity and the dynamic states of their rotor, DC capacitor, AC windings, and filter inductance have relatively low time constants [18]. Consequently, the state prediction for the DSE approaches may be inaccurate, as the DSE time step is large, e.g., consistent with the PMU reporting rate of 50 or 60 samples per second [19].…”
Section: Introductionmentioning
confidence: 99%